2020
DOI: 10.1136/bmjopen-2019-036098
|View full text |Cite
|
Sign up to set email alerts
|

Using Baidu search index to monitor and predict newly diagnosed cases of HIV/AIDS, syphilis and gonorrhea in China: estimates from a vector autoregressive (VAR) model

Abstract: ObjectivesInternet search engine data have been widely used to monitor and predict infectious diseases. Existing studies have found correlations between search data and HIV/AIDS epidemics. We aimed to extend the literature through exploring the feasibility of using search data to monitor and predict the number of newly diagnosed cases of HIV/AIDS, syphilis and gonorrhoea in China.MethodsThis paper used vector autoregressive model to combine the number of newly diagnosed cases with Baidu search index to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This study found that OMC and OMS were the Granger causes of confirmed cases during the outbreak of COVID-19, whereas OMA was not. The predictive power of OMS was not surprising, as it is in line with the Google Flu studies ( Dugas, Jalalpour, Gel et al., 2013 ; Martin, Lee, Yasui, 2016 ) and other Baidu search index studies ( He, Chen, Chen et al., 2018 ; Huang et al., 2020 ). However, the predictive value of OMS in this study was lower than that of OMC – an underexplored online medical behavior.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This study found that OMC and OMS were the Granger causes of confirmed cases during the outbreak of COVID-19, whereas OMA was not. The predictive power of OMS was not surprising, as it is in line with the Google Flu studies ( Dugas, Jalalpour, Gel et al., 2013 ; Martin, Lee, Yasui, 2016 ) and other Baidu search index studies ( He, Chen, Chen et al., 2018 ; Huang et al., 2020 ). However, the predictive value of OMS in this study was lower than that of OMC – an underexplored online medical behavior.…”
Section: Discussionsupporting
confidence: 80%
“…In present study, we applied the VAR model for multivariate time series analysis to capture their dynamic interdependence by taking each variable as the linear function of past lags of itself and the past lags of the other explanatory variables ( Hamilton, 1994 ; Lütkepohl, 2006 ). Recent studies used VAR models to predict the trend of infection diseases such as sexually transmitted diseases ( Huang, Luo, Duan et al., 2020 ), Dengue ( Ramadona, Lazuardi, Hii et al., 2016 ) and the ongoing COVID-19 ( Khan, Saeed, Ali et al., 2020 ; Khan, Saeed, Ali et al., 2020 ; Fantazzini, 2020 ). A basic VAR model contains a set of n endogenous variables y t = ( y 1 t , y 2 t , …, y n t ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu et al [ 30 ] found that the erythromelalgia epidemic search index showed the uptrend about a week ahead of the official report because of the delayed reports from the local Center for Disease Control and Prevention. Future research can establish relevant models, including the vector autoregressive model, to predict the future trend of the epidemic based on past values of the real-world data [ 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies mainly used daily new cases for time-delay correlation [16,22,[27][28][29][30][31][32][33], while this study used new cases and confirmed cases. For confirmed, death, and cured discharge cases, new variables are the number of cases that increased in 1 day, and cumulative variables are the superposition of all the case data up to that day.…”
Section: Bdi Has Significant Temporal Difference With Real-world Datamentioning
confidence: 99%